A medicinal chemistry approach to drug repositioning in the treatment of tuberculosis and malaria - Kaur, Gurminder (Department of Chemistry, 2017)
Tuberculosis (TB) and malaria continue to be major public health concerns, globally claiming 2-3 million deaths every year. A number of efficacious drugs are available for the treatment of TB and malaria, which, through various combination therapies, are fully effective in treating these diseases. However, the wide spread resistance in M. tuberculosis (Mtb) and P. falciparum, the causative agents of TB and malaria, respectively, has made the existing therapies less effective. Thus novel agents able to circumvent drug resistance and other challenges associated with existing TB and malaria treatments are urgently needed. The development of a new drug is a lengthy and costly process; therefore, approaches that can save both time and money need to be emphasised. Drug repositioning is one such approach that has been applied in this project. Drug repositioning basically involves a situation where a drug active in one disease is derivatised or used as a template for the synthesis of derivatives active in another disease. This approach has the potential to significantly shorten the drug discovery process. This study focused on the repositioning of two drugs, the antibacterial agent fusidic acid and the antipsychotic agent metergoline, in TB and/or malaria via medicinal chemistry approaches. New semisynthetic derivatives of fusidic acid and metergoline were synthesized and evaluated for antimycobacterial activity against the H37Rv strain of Mtb and antiplasmodial activity against the NF54 strain of P. falciparum.